Assessment of Uruguayan Oil Shales: physicochemical, thermal and morphological characterization. (15th December 2018) - Torres, Martín; Castiglioni, Jorge; Yermán, Luis; Suescun, Leopoldo; Conti, Bruno; Demarco, Manuela Morales; Gristo, Pablo; Portugau, Patrice; Cuña, Andrés
Highlights: Combustion kinetics of the Uruguayan Oil Shale was investigated. XRD test identified the minerals present in the Oil Shale and their ashes. The Oil Shale has high TOC content, suggesting a marine depositional environment. The kerogen is characterized by predominantly type II. The Uruguayan Oil Shale has the potential of being used in co-combustion processes. Abstract: Oil shales from Mangrullo Formation (Uruguay) was assessed as a potential fuel for energy production. The assessment is based on a comprehensive characterization of the material from a thermal perspective. Co-combustion of this type of fuel with biomass waste can enhance the combustion performance and decrease hazardous gas emissions. The low heating value (3.2 MJ kg −1 ) of the Uruguayan oil shale indicates that it could be mixed with biomass to obtain better results. Stratified sampling of drill cores was used to obtain a representative sample. The morphological and structural characteristics of the oil shale were studied by X-ray diffraction and scanning electron microscopy. Chemical composition (hydrocarbons and minerals) of oil shales was investigated by X-ray diffraction, X-ray fluorescence, proximate and ultimate analysis and Fourier transform infrared spectroscopy. Rock Eval analysis was performed to measure richness and maturity of the Uruguayan oil shale, the results of the TOC content (8.93%) and the hydrogen index (525 mg HC/ g TOC) indicated that it constitutes an excellent source rock. The kinetic of the combustion and thermal properties of oil shale were studied. The activation energy of the different reaction stages was calculated using the Flynn-Wall-Ozawa model, then we obtained the pre-exponencial factor and the reaction order optimizing the theoretical model using the experimental data. Results indicated that the combustion of the oil shale exhibits multiple reaction stages with activations energies that varies between 152.2 and 316.4 kJ mol −1 .